2020
DOI: 10.3389/fchem.2020.622325
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Synthesis of D-Allulose Using Novel D-Tagatose 3-Epimerase From Christensenella minuta

Abstract: D-allulose, which is one of the important rare sugars, has gained significant attention in the food and pharmaceutical industries as a potential alternative to sucrose and fructose. Enzymes belonging to the D-tagatose 3-epimerase (DTEase) family can reversibly catalyze the epimerization of D-fructose at the C3 position and convert it into D-allulose by a good number of naturally occurring microorganisms. However, microbial synthesis of D-allulose is still at its immature stage in the industrial arena, mostly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 45 publications
(60 reference statements)
1
14
0
Order By: Relevance
“…1). The polygenetic tree of the KEase family obtained by the neighbor-joining method (Wang et al, 2021) indicated a close relationship of CDAE to other DAEases; in particular, an evolutionary relationship between CDAE and the DAEases from Clostridium cellulolyticum H10 (Clce-DAE; GenBank ACL75304.1; Mu et al, 2011) and Clostridium sp. BNL1100 (Clsp-DAE; GenBank WP_014314767.1; Mu et al, 2013).…”
Section: Sequence Analysismentioning
confidence: 99%
“…1). The polygenetic tree of the KEase family obtained by the neighbor-joining method (Wang et al, 2021) indicated a close relationship of CDAE to other DAEases; in particular, an evolutionary relationship between CDAE and the DAEases from Clostridium cellulolyticum H10 (Clce-DAE; GenBank ACL75304.1; Mu et al, 2011) and Clostridium sp. BNL1100 (Clsp-DAE; GenBank WP_014314767.1; Mu et al, 2013).…”
Section: Sequence Analysismentioning
confidence: 99%
“…Notably, only the DPEase from Dorea sp. CAG317 and the DPEase from C. minuta are optimally adapted to weak acidic pH conditions [24,25], suggesting that these two enzymes have potential for application in the large-scale production of D-allulose. Note: NR = not reported.…”
Section: Source Of Enzymesmentioning
confidence: 99%
“…Most of them are weakly basophilic [ 22 , 23 ], except for Dorea sp. CAG317 d -psicose 3-epimerase (DPEase) and Christensenella minuta DPEase, which posess a weakly acidic optimal pH [ 24 , 25 ]. Ketose 3-epimerases have been heterologously expressed successfully in prokaryotic and eukaryotic systems for the efficient production of D-allulose and its high-value derivates.…”
Section: Introductionmentioning
confidence: 99%
“…The Izumoring strategy is an effective method proposed in 2006 for the bioproduction of various kinds of rare hexoses [ 18 ] and also involves D-allulose 3-epimerase (DAE), D-tagatose 3-epimerase (DTE), polyol dehydrogenases, and aldose isomerases [ 19 ]. Consequently, D-fructose can be epimerized at the C-3 position to produce D-allulose by DTEs or DAEs [ 20 ]. Due to the substrate specificity, catalytic property, and specific enzyme activity of D-tagatose epimerase and D-allulose epimerase being different enzymes and are named DTE and DAE, respectively [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to one study, DTE extracted from the genes found in the macro-genome resource of the hot water exhibited high thermostability at 60 °C to 70 °C [ 35 ]. Probiotics are also sources of several DTEs, including the DTE-CM gene from Christensenella minuta DSM 22607 [ 20 ], which is produced in accordance with food safety regulations.…”
Section: Introductionmentioning
confidence: 99%